Small Cell Neuroendocrine of the Head and Neck: A Rare Presentation and Review of the Literature - Stephanie Niforatos MD; Michael Sandhu MD; Mansi Kallem MD; Serenella Serinelli MD, PhD; Christopher Curtiss MD; Komal Akhtar MD (SAGE Publishing, 2022)
Head and neck tumors account for roughly 3% of malignancies in the United States and about 90% of these tumors are squamous cell cancers. Neuroendocrine neoplasms arise from neural crest cells and are commonly found in the gastrointestinal tract. Neuroendocrine neoplasms arising from the head and neck tend to be rare. In this article, we present a rare case of human papilloma virus-associated poorly differentiated small cell neuroendocrine carcinoma (NEC). Our patient was a 62-year-old African American man who presented with worsening left-sided neck pain and swelling that started 3 months prior to presentation, associated with an unintentional 20-pound weight loss over 6 months, hoarseness in his voice, in addition to dysphagia and odynophagia. Biopsy of left-sided tongue mass revealed poorly differentiated small cell NEC that was positive for HPV (E6/E7) RNA in situ hybridization. Patient was found to have metastatic disease at the time of diagnosis and given the aggressive nature of small cell NECs and the patient's symptomatic burden, chemotherapy with cisplatin and etoposide was initiated in the hospital. The patient was subsequently discharged from the hospital and is continuing treatment outpatient with cisplatin, etoposide, and atezolizumab.